1990
DOI: 10.1152/ajpheart.1990.258.2.h529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atherosclerosis on the coronary microcirculation

Abstract: We tested the hypothesis that atherosclerosis potentiates coronary vasoconstriction to serotonin and ergonovine. Coronary microvascular pressures and diameters were measured in the beating left ventricle in normal and atherosclerotic cynomolgus monkeys. Pressures were measured in arteries (190-350 microns diam) that were distal to atherosclerotic lesions. Microvascular pressure and simultaneous measurements of aortic pressure and myocardial blood flow were used to calculate segmental vascular resistance (large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…4,5,10,25 In the present study, we demonstrated for the first time the presence of endothelial dysfunction in isolated human coronary resistance vessels from patients with severe atherosclerosis. So far, the underlying reasons and the pathophysiological significance of endothelial dysfunction remain unclear.…”
Section: Physiological and Pathophysiological Implicationssupporting
confidence: 55%
“…4,5,10,25 In the present study, we demonstrated for the first time the presence of endothelial dysfunction in isolated human coronary resistance vessels from patients with severe atherosclerosis. So far, the underlying reasons and the pathophysiological significance of endothelial dysfunction remain unclear.…”
Section: Physiological and Pathophysiological Implicationssupporting
confidence: 55%
“…The mechanisms underlying abnormal endothelium-dependent vascular relaxation in atherosclerosis may include decreased or abnormal production and/or release of endothelium-derived relaxing factor, destruction of endothelium-derived relaxing factor, and the concomitant release of constricting factors. 39,41 A recent clinical study suggests that in patients with atherosclerosis, production of endothelium-derived cyclooxygenase-dependent constricting factors contributes to the abnormal acetylcholine-mediated dilation of the peripheral artery, which has no atherosclerotic lesions. 45 In addition to renal artery stenosis induced by atherosclerosis, endothelial dysfunction may also contribute to renovascular hypertension in Apoe -/-animals.…”
Section: Apoementioning
confidence: 99%
“…This agrees with earlier studies of large coronary arteries of hypercholesterolemic rabbits 5 and the coronary circulation of atherosclerotic nonhuman primates. 15 The abnormal response to 5-HT of the PCs could be associated with endothelial dysfunction, in the form of either impaired release of EDRF or release of a constricting factor from the endothelium. In normal PC segments, we found that endothelial removal increased the maximum response to 5-HT, which is consistent with responses in porcine and canine PCs.…”
Section: Increased Vasoconstriction To Serotonin In Large Atheromatoumentioning
confidence: 99%